Marginality, exclusion, and social justice - Saxena, Ashish (Jaipur : Rawat Publications, 2013)
With reference to India; papers presented at workshop held in 2009.
Includes bibliographical references and index.
Keywords: MARGINALITY, SOCIAL -- INDIA -- CONGRESSES; SOCIAL JUSTICE -- INDIA -- CONGRESSES